Psychosocial Impact of Hirsutism in Female Patients Attending Dermatology OPD of CMH Kharian - Nazar, Warda; Minhas, Azhar Hosain; Shafi, Sundas; Batool, Maryam; Sarwar, Amara; Ibrar, Mahjabeen (Indus Journal of Bioscience Research, 2025)
Background and Aim: Hirsutism in women leads to substantial psychological and social issues. It adversely affects women's quality of life, causing stress, anxiety, and depression. The present study aimed to determine the psychosocial impact of hirsutism in female patients. Patients and Methods: This cross-sectional study investigated 126 female patients suffering from hirsutism who attended the dermatology unit of Combined Military Hospital, Kharian from May 2024 to October 2024. Female patients aged 16-50 years of different classes having Hirsutism were included. A specially designed questionnaire was used for data collection. Baseline details such as age, marital status, educational and employment status, and psychosocial effects in terms of normal and abnormal due to hirsutism were recorded. SPSS version 26 was used for descriptive statistics. Results: The overall mean age was 28.8±8.26 years. The psychosocial effect (Abnormal) was found in 102 (81%) patients. Age-wise distribution of patients was as follows; 68 (54%) in 16-30 years, 40 (31.7%) in 31-45 years, and 18 (14.3%) in 46-50 years. There were 102 abnormal and 24 normal patients. The distribution of abnormal and normal psychosocial effects among different age groups were as follows; 58 (85.3%) vs. 10 (14.7%) in 16-30 years, 32 (80%) vs. 8 (20%) in 31-45 years, and 12 (66.7%) vs. 6 (33.3%) in 46-50years. A standard scale used for depression and anxiety found that 72 (70.6%) female experienced moderate to severe anxiety whereas 16 (15.7%) had borderline anxiety. Conclusion: It has been observed that patients with hirsutism often experience psychosocial influences that can lead to anxiety and depression. These psychosocial influences are most prevalent among young, working, and unmarried women.